Men's Short-term Experience of Acquired Physical Disabilities in Japan - Masakuni Tagaki (Disability Studies Quarterly, 2011)
This study examines the life-changing implications of acquired physical disability from a short-term perspective. The participants consisted of 14 men, each of whom had sustained a spinal cord injury on an average of five years before the study. A semi-structured interview was conducted twice with each participant in order to outline the characteristics of his post-injury life. No participant over-estimated the influence of disability on his life; some participants stated that the disadvantages they faced could be attributed to things other than their disabilities. They developed social identities as people with acquired disabilities through their relationships with others with similar disabilities. To alleviate their sense of loss, the participants emphasized unchanged aspects of their pre-injury lives.
Keywords: disability; Japan; illness and disease; experiences; life stories; spinal cord injury